Sustainability of the Bioenergy Agricultural Frontier in the Brazilian Amazon:: an overview - Lameira, Wanja Janayna de Miranda; Vieira, Ima Célia Guimarães; Toledo, Peter Mann de (Sustainability in Debate, 2015)
This study presents an overview of the sustainability levels in seven municipalities in the Brazilian state of Pará that are included in the oil palm production zone (Elaeis guineensis Jacq.), in Eastern Amazon. The area, of approximately 46,000 km², presents different patterns of land use, and is currently considered as a priority for the implementation of the Brazilian national policy of biofuels due to its favorable edafoclimatic conditions. The study is an ex ante evaluation of the sustainability levels of the municipalities in Pará using a Sustainability Barometer - SB. The authors used quantitative data from secondary sources dated from 2010 on, all adjusted to the conceptual framework of the SB. Sixteen indicators were used to measure human well-being (social indicators) and nine indicators for the ecological well-being (environmental indicators). Results showed that all the analysed municipalities occupy intermediate and potentially unsustainable positions in the SB scale, which reflects the socioeconomic and environmental fragility of the studied area.